The Effect Of Solvency Ratio, Profitability Ratio And Activity Ratio To Company Value Of PT. Astra Internasional Tbk - Ida Yusnita (Citakonsultindo, 2023)
This study aims to determine the effect of Solvency Ratio proxied by Debt to Equty Ratio (DER), Profitability Ratio proxied by Return On Assets (ROA) and Activity Ratio proxied by Total Assets Turn Over (TATO) on Firm Value proxied by Price to Book Value (PBV), partially and simultaneously. This study explains the factors that affect the Firm Value. These factors are the Solvency Ratio, Profitability Ratio and Activity Ratio. The data used in this study is secondary data, namely Summary of Financial Statement data obtained from the financial statements of PT. Astra International Tbk, which is listed on the Indonesia Stock Exchange for the period 2011-2021. Based on the results of data analysis that has been carried out on all the data obtained, it can be concluded as follows: 1). Solvency ratio has no partial and insignificant effect on firm value, as evidenced by tcount (1,771) < t¬table (2,365) and the value of Sig. = 0,120 > 0,05 so that hypothesis I cannot be accepted. 2). Profitability ratios have no partial and insignificant effect on firm value, as evidenced by tcount (0,402) t table (2,365) and the value of Sig. = 0,700 > 0,05 and so hypothesis II cannot be accepted. 3). The activity ratio has no partial and insignificant effect on firm value, as evidenced by t count (1,127) t table (2,365) and the value of Sig. = 0,297> 0 05 and so hypothesis III cannot be accepted. 4). Solvency Ratio, Profitability Ratio and Activity Ratio have a simultaneous and significant effect on firm value, as evidenced by the value of Sig. = 0 03 > 0,05 and f count (193,435) t table (4,35) so that the fourth hypothesis can be accepted.